Pullulan dialdehyde crosslinked gelatin hydrogels with high strength for biomedical applications. (15th July 2019) - Zhang, Liru; Liu, Jie; Zheng, Xuejing; Zhang, Ali; Zhang, Xianliang; Tang, Keyong
Graphical abstract: Highlights: A high-strength pullulan dialdehyde (PDA) crosslinked gelatin hydrogel was synthesized. The hydrogel strength was adjusted by controlling the concentration of PDA. The swelling and enzymatic degradation of the hydrogel were limited by PDA crosslinking. The hydrogel exhibited non-cytotoxicity. Abstract: Herein the construction of a strong gelatin hydrogel is presented by using pullulan dialdehyde (PDA) as a macromolecular crosslinker. The resultant PDA crosslinked gelatin hydrogels (G-PDA) exhibit extremely high mechanical strength, manifested in the achieved optimal compressive stress of 5.80 MPa at 80% strain, which is up to 152 times higher than pure gelatin hydrogel. The G-PDA were characterized by Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The extent of crosslinking was determined by ninhydrin assay. The results suggested that the synergistic effect of dual-crosslinking, which is composed of short- and long-range covalent crosslinking and thermoreversible physical crosslinking, may played a key role in enhancing the load-bearing capacity of ensuing hydrogels. The swelling and enzymatic degradation of G-PDA are gradually limited with increasing PDA concentration. The result from MTT assay demonstrated that G-PDA is non-cytotoxic against MC3T3 cells, regardless of the concentrations of PDA.